The benefits of discourse analysis for Human Resource Management - Julia Hormuth (Zeitschrift für Personalforschung (ZfP), 2009)
The objective of this article is to take a closer look at discourse analysis as a qualitative method of data collection, analysis and theory building in Human Resource Management. Working exclusively with audio or video recordings of authentic conversations and following a systematic methodological process, discourse analysis enables researchers to develop theoretical conclusions and models on HR topics. First, basic assumptions and tools of discourse analysis are presented. Special emphasis is put on the applied discourse analytical approach and potential benefits for research on Human Resource Management. Second, drawing on a research project carried out at the University of Bayreuth, an example is presented of how discourse analysis was used to investigate experience management. The project yielded a theoretical model that describes the communicative processes of experience transfer among expatriate managers. It reveals the particular challenges involved as well as strategies interactants use to cope with them. Being strictly action-oriented, the model is advantageous for deducing recommendations for Human Resource Development. – – Ziel dieses Artikels ist es, die Leistungen der Gesprächsanalyse als qualitative Methode der Datenerhebung, Auswertung und Theoriebildung im Personalmanagement aufzuzeigen. Die Gesprächsanalyse arbeitet ausschließlich mit Ton- und Videoaufnahmen authentischer Gespräche und folgt dabei einem systematischen methodischen Vorgehen, das es dem Forscher ermöglicht, theoretische Schlussforderungen und Modelle zu Personalmanagementthemen zu entwickeln. Zunächst werden grundlegende Annahmen und Werkzeuge der Gesprächsanalyse vorgestellt. Ein Schwerpunkt liegt auf der angewandten Gesprächsforschung und dem Nutzen für die Forschung im Bereich des Personalmanagements. Anhand eines Projekts an der Universität Bayreuth wird aufgezeigt, wie die Gesprächsanalyse genutzt werden kann, um Strategien des Erfahrungsmanagements zu erforschen. In dem Projekt wurde ein theoretisches Modell der kommunikativen Prozesse der Erfahrungsweitergabe unter Auslandsentsandten entwickelt. Es beschreibt die spezifischen Herausforderungen, die sich für Gesprächspartner ergeben, sowie Strategien, die sie zu ihrer Bewältigung verwenden. Das strikt handlungsorientierte Modell bietet eine gute Grundlage, um Empfehlungen für die Personalentwicklungspraxis abzuleiten.
Keywords: 330; discourse analysis; communication; knowledge management; transfer of experiences; expatriates; Personalmanagement; Diskursanalyse